Colonial liquor laws - Thomann, G. (Gallus) (United States Brewers' Association, 1887)
Includes "an historical outline of the origin, spirit and effects of the liquor-laws, as well as of the habits and circumstances of the people of Massachusetts, Virginia, New York, New Jersey and Pennsylvania; and will readily perceive that in regard to Connecticut, Rhode Island, Maryland, the Carolinas, and Georgia, tha author has endeavored to avoid repetitions, by confining his review to the particular features in which the laws of the latter colonies differed from those of the former."